Enhanced photoresponse in ZnO nanorod array/p-GaN self-powered ultraviolet photodetectors via coupling with CuO nanostructures. (20th January 2020) - Fu, Qiu-Ming; Yao, Zhi-Chao; Peng, Ji-Liang; Zhao, Hong-Yang; Ma, Zhi-Bin; Tao, Hong; Tu, Ya-Fang; Zhou, Di; Tian, Yu
Abstract: ZnO nanorod arrays (ZnO NRAs) coupled with coral-like CuO nanostructures (CuO CLNs) were prepared by low-temperature hydrothermal method. Self-powered ultraviolet (UV) photodetectors (PDs) based on ZnO NRAs/CuO CLNs/p-GaN heterostructure were fabricated via a direct-contact method. Under UV illumination (1.46 mW cm −2 ), the ratios of photocurrent to dark current ( I photo / I dark ), photo-responsivity and specific detectivity for the ZnO NRAs/CuO CLNs/p-GaN heterojunction self-powered PD were estimated to be 1143, 1.44 mA W −1 and 5.9 × 10 10 cm H z 1 /2 /W at 0 V, which were about ∼187, ∼104 and ∼153 times greater than those of the ZnO NRAs/p-GaN self-powered PD, respectively. Moreover, the PD displayed faster response time, excellent stability and repeatability by coupling with CuO CLNs. The mechanism of the enhanced photoresponse performance was discussed through the energy band diagram.